A docência como obra de arte : um estudo com professores da educação superior - Santana, Lilian Rose Aguiar Nascimento Garcia de (2013)
This work is about a doctoral research on Culture, Memory and Theories in education. The research is of a philosophic-educational perspective about the formation of teachers of higher education, conceived here as the constitution of teaching styles. The question that moves the work is: how does someone become a what is, it’s born of the philosophical thought of Friedrich Nietzsche, especially the concept of life-experience. To approach of the object, is done in dialogue with the production of Selma Garrido Pimenta to understand the formation of teachers of higher education. The thesis defended in this work is that the teaching is made of unique styles, although we find common elements to be of the teacher. Logic underpins this procedure: the implications of life for reflection, or, in this case, for the constitution of the teaching style. Thus, this work seeks to operate an inversion of perspective: look at the formation of teachers of higher education from the teachers, their life, that is, teaching as an art style. To do this, whether it is the concept of otobiography created by Jacques Derrida, redesigned by Silas Borges Monteiro, as the operator element analysis of interviews with teachers, collaborators of this work.